2014
DOI: 10.1002/jbmr.2408
|View full text |Cite
|
Sign up to set email alerts
|

TSH Elevations as the First Laboratory Evidence for Pseudohypoparathyroidism Type Ib (PHP-Ib)

Abstract: Hypocalcemia and hyperphosphatemia because of resistance towards parathyroid hormone (PTH) in the proximal renal tubules are the most prominent abnormalities in patients affected by pseudohypoparathyroidism type Ib (PHP-Ib). In this rare disorder that is caused by GNAS methylation changes, resistance can occur towards other hormones, such as thyroid-stimulating hormone (TSH), that mediate their actions through G protein-coupled receptors. However, these additional laboratory abnormalities are usually not recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 41 publications
2
30
1
1
Order By: Relevance
“…By contrast, patients with PHP1B show abnormal patterns of methylation in the DMRs associated with the GNAS complex locus 45,47,[86][87][88]101,143,[151][152][153][154] . A methylation defect can be classified as partial or complete and can affect one or multiple DMRs within 20q13 (reF.…”
Section: Molecular Diagnosismentioning
confidence: 92%
See 4 more Smart Citations
“…By contrast, patients with PHP1B show abnormal patterns of methylation in the DMRs associated with the GNAS complex locus 45,47,[86][87][88]101,143,[151][152][153][154] . A methylation defect can be classified as partial or complete and can affect one or multiple DMRs within 20q13 (reF.…”
Section: Molecular Diagnosismentioning
confidence: 92%
“…Subsequent analyses have demonstrated that some patients with PHP1B display additional features that overlap with PHP1A. As in PHP1A, PTH resistance might not be present at birth and develops only over time [44][45][46][47][48][49][50] . TSH resistance and patterns of excessive intrauterine growth or weight gain at birth or during early infancy and childhood have been described 44,51,52 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations